Status and Inheritance Rights of Assisted Reproductive Technology Conceived-Child: An Islamic Law Perspective - Ibrahim Yahaya Abikan (Asy-Syari'ah, 2024)
Abstract: This paper discusses the status of children born through assisted reproductive technology (ART) and its implications for inheritance rights from the Islamic Law perspective. For comprehensive and supporting debate, this section explains the types of ART, such as artificial insemination, in vitro fertilization, sperm donors/egg banks, and surrogacy. This paper adopts a doctrinal research method by conducting an in-depth analysis of primary and secondary legal sources. Then, the arguments of Muslim scholars on the topic are analyzed. Results show that legal experts disagree on whether the egg donor or the woman who conceives and gives birth is the biological mother based on the surrogacy regulation for children’s rights to inheritance. The author argues that if semen and eggs from a legally married couple are reproduced through ART, the child will be legitimate to the marriage and have full rights to inherit from both parents. However, if a third person is involved either through artificial insemination, surrogate motherhood, or in vitro fertilization, the child is walad al-zina (illegitimate child), who cannot inherit from the father but only from the mother and her relatives. This research contributes to the development of contemporary Islamic Law, which faces increasingly complex problems in this technological era.